Advanced nanomaterials synthesis from pyrolysis and hydrothermal carbonization: A review - Nizamuddin, S.; Siddiqui, M.; Mujawar, Mubarak; Baloch, H.; Mazari, S.; Tunio, M.; Griffin, G.; Srinivasan, M.; Tanksale, A.; Riaz, S. (Bentham Science Publishers Ltd., 2018)
Background: Carbon-based structural materials are widely studied in the field of renewable energy and environmental sciences. Utilization of abundant, natural, renewable energy precursors together with simple and low energy processes can contribute to reduced emissions of greenhouse gas so is considered as fundamental for manufacturing of sustainable nanostructured materials. Description: Among different resources available for the generation of nanostructured materials, plant biomass is superior in terms of economic, environmental and social issues. In addition, transformation of low-value biomass to emerging renewable materials is advantageous compared to dumping and incinerating the biomass. There are a number of techniques and processes for the production of nanostructured materials from biomass. Pyrolysis and hydrothermal carbonization (HTC) may be used to convert biomass into nanostructured materials. Objective: This study reviews and compares the production of nanostructured materials from pyrolysis and HTC. Furthermore, the latest developments in pyrolysis and HTC for nanomaterials production are assessed and comparative characteristics are studied for nanomaterials obtained.